the Chacal de Nahueltoro, a social history chapter (Andamios, Revista de Investigación Social, 2015)
The film El Chacal de Nahueltoro can be analyzed as an exploration of the past from the discourse of cinema. Filmed in 1969, the movie recreates events actually occurred in 1960, but also questions the Chilean social structure and the existence of patterns of domination in the country originated in colonial times. That issue was brought to the screen after a documentary work made by director Miguel Littín and his crew, much like the kind of work done by historians, although favoring an understanding of the historical matter that shed light on the experience and voice of subaltern subjects.
Keywords: El Chacal de Nahueltoro; Miguel Littín; social history; Chilean cinema; film-history relationship